2019
DOI: 10.1002/pmh.1447
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitively oriented psychotherapy for schizotypal personality disorder: A two‐case series

Abstract: Schizotypal personality disorder represents a broad range of maladaptive behaviour, which has been linked to both personality disorder and schizophrenia spectrum disorders; however, to date, little effort has been devoted to developing psychosocial treatment approaches to address it. In response, we conducted two case studies exploring the effects of two metacognitively oriented forms of psychotherapy: metacognitive interpersonal therapy and metacognitive reflection and insight therapy for patients with schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 58 publications
4
31
0
1
Order By: Relevance
“…A final source of evidence for MERIT comes from published case studies. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] While susceptible to selection and confirmation bias, case studies present important idiographic and clinical information about unique and subjective experiences which can potentially complement other evidence and be synthesized into a larger understanding of this treatment approach. Table 1 presents 15 MERIT case studies (describing 16 individuals in total) which provide rich descriptions of patients' problems, goals, and treatment outcomes, as well as changes in metacognition as measured by the MAS-A.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A final source of evidence for MERIT comes from published case studies. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] While susceptible to selection and confirmation bias, case studies present important idiographic and clinical information about unique and subjective experiences which can potentially complement other evidence and be synthesized into a larger understanding of this treatment approach. Table 1 presents 15 MERIT case studies (describing 16 individuals in total) which provide rich descriptions of patients' problems, goals, and treatment outcomes, as well as changes in metacognition as measured by the MAS-A.…”
Section: Case Studiesmentioning
confidence: 99%
“…(Two case studies of persons diagnosed with Borderline Personality Disorder were also included who had experienced transient psychosis and functioned at levels commonly found in persons with psychosis.) There is also an additional case study 70 which reported the successful delivery of MERIT to an adult diagnosed with Schizotypal Personality Disorder, again without adverse effects and with clinically significant improvement.…”
Section: Case Studiesmentioning
confidence: 99%
“…It may be, for example, that if perspective taking erodes with the course of psychosis, interventions are needed that help preserve this in early episode psychosis. To date, one of these, metacognitive reflection and insight therapy, has been found to be acceptable by participants in locations including Australia (Bargenquast & Schweitzer, 2013), Italy (Cheli et al, 2019), the Netherlands (de Jong et al, 2018), France (Dubreucq et al, 2016), and Israel (Hasson‐Ohayon et al, 2017) and investigations are currently ongoing into its adaptation in urban Russia.…”
Section: Discussionmentioning
confidence: 99%
“…First, metacognition, as operationalized using the MAS-A, diverges from social cognition and mentalizing research in its emphasis, consistent with work on personality disorders [ 24 , 111 113 ], that the senses of self and others that are disturbed in psychosis involve automatic and purposeful processes in which embodied, affective and cognitive experiences are not successfully integrated into a larger sense of the self or others. Metacognitive research thus distinctively resists framing the experience of the self and others as fundamentally modular or the product of different dissociable processes.…”
Section: The Unique Experimental Theoretical and Clinical Implications Of Metacognitive Research In Psychosismentioning
confidence: 93%